Islamic Reformism and Christianity A Critical Reading of the Works of Muḥammad Rashīd Riḍā and His Associates (1898-1935) - Ryad, Umar (The History of Christian-Muslim Relations, 2009)
Drawing on newly-discovered archival materials, the study offers a comprehensive and critical reading of the polemics of Sheikh Rashīd Riḍā and his associates on Christianity in al-Manār, and their fascinating encounters with Arab Christians and Christian missionary movements.